تعلم وتكلم : الكتاب 2 (Ta'allam Wa Takallam : al-Kitab 2) - Abdul Maqsud, Hasan; Chik, Abdul Rahman; Hayaza, Abdul Karim awadh; Haji Hitam, Saidi (Language Centre, Universiti Brunei Darussalam, 2004)
Learn to speak Arabic language